Remote sensing for monitoring embankments, dams, and slopes : recent advancements - Bouali, El Hachemi; Gregory, Phillip; Leshchinsky, Ben; Arasa, Nuria Devanthery; Hughes, Stephen; Praeg, Robert; Sathyan, Sajin Kumar Kochappi; Villarreal, Andres (American Society of Civil Engineers, 2021)
Sponsored by the Embankments, Dams, and Slopes Technical Committee of the Geo-Institute of ASCERemote Sensing for Monitoring Embankments, Dams, and Slopes: Recent Advances, GSP 322, provides information on selecting and deploying a monitoring network to assess the behavior, geometry, total and differential EDS movement, and potential risks of the EDS movement on people and infrastructure.Topics include general technologies used for EDS monitoring, selection and installation of networked sensors for predictive analytics and image recognition, application of monitoring techniques in the design of early warning systems, case studies, and support for decision-makers in implementing early warning systems.Information on a broad range of technologies, such as radio detection and ranging (radar), synthetic aperture radar (SAR), interferometric synthetic aperture radar (InSAR), light detection and ranging (LiDAR), digital photogrammetry and image processing, microelectromechanical systems (MEMS), automatic motorized total stations (AMTS), and unmanned aircraft systems (UAS) to deploy the remote sensing technologies is also included.This Geotechnical Special Publication will be useful to both practitioners and researchers to understand and utilize currently available remote sensing technology and to advance and refine the monitoring of embankments, dams, and slopes.
Keywords: Embankments -- Remote sensing.; Dams.; Slopes (Soil mechanics) -- Remote sensing.; Dam safety.; Soil stabilization.; elektronické knihy; electronic books